A facile approach for the synthesis of highly luminescent carbon dots using vitamin-based small organic molecules with benzene ring structure as precursors. Issue 110 (22nd October 2015) - Zheng, Yawen; Yang, Dan; Wu, Xin; Yan, Haoran; Zhao, Yuancong; Feng, Bo; Duan, Ke; Weng, Jie; Wang, Jianxin
Abstract : In this study, vitamin-based small organic molecules were used as precursors to synthesize carbon dots by means of a hydrothermal approach. Abstract : In this study, vitamin-based small organic molecules were used as precursors to synthesize carbon dots by means of a hydrothermal approach. The obtained carbon dots presented high luminescence and good cellar-imaging properties when folic acid was used as a precursor and the quantum yield of the carbon dots obtained using the present method was more than 30%. Moreover, green and yellow-green photoluminescence was also successfully achieved by adding the reagents H3 PO4 and H2 C2 O4, respectively. The related formation mechanism and photoluminescence emission mechanism of carbon quantum dots were discussed. The present study will open a new possible route for the synthesis of carbon dots with high quality using small organic molecules as precursors.